Penerapan Metode Quality of Service (QoS) dalam Analisis Kualitas Jaringan Internet Burjo Pantry Semarang - Pamungkas, Bima; Sutanto, Felix Andreas (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The rapid progression of technology enables humans to exchange data and communicate remotely, eliminating the need for face-to-face interactions. The internet network, a product of this technological advancement, undergoes evaluation through the Quality of Service (QoS) method, which measures network service quality. This research focuses on assessing the internet network quality at Burjo Pantry in Semarang, utilizing a quantitative approach with a Quality of Service analysis. The throughput results reveal 1682Kbps in the terrace area and 7266Kbps indoors at Burjo, both categorized as 'very good.' Likewise, the delay, with 128,75ms in the terrace and 145ms indoors, falls into the 'very good' category. Both areas exhibit excellent jitter: 1,77ms for the terrace and 26,46ms indoors. Packet loss is minimal, with 1,73% in the terrace area and 0,68% indoors, both considered 'very good.' Overall, the study indicates the commendable quality of the internet network at Burjo Pantry in Semarang.
Keywords: QoS; WLAN; Delay; Jitter; Packet Loss; Throughput